Optimalisasi Insentif Pajak Terhadap Instrumen Sukuk Ijarah Dalam Pengembangan Pasar Modal Syariah Indonesia - Nur Laily Hidayati; Zakiyyah Ilma Ahmad; Kevin Maulana; Jafar Shiddiq (Faculty of Islamic Economics and Business, 2026)
This study aims to analyze the effectiveness of tax incentives on the development of Sukuk Ijarah in Indonesia, specifically during the 2023–2024 observation period. Sukuk Ijarah, as a key instrument in the Islamic capital market, still faces the challenge of potential double taxation due to the application of VAT and income tax on the underlying asset, which may reduce its competitiveness compared to conventional bonds. This study uses a qualitative descriptive method utilizing secondary data sourced from issuer reports, Financial Services Authority (OJK) publications, and applicable tax regulations for the 2023–2024 period. The analysis focuses on evaluating the tax incentive policies provided by the government and their impact on issuer and investor interest in Sukuk Ijarah issuance. The results indicate that despite an increasing trend in sukuk issuance during the study period, the effectiveness of tax incentives has not been fully optimized. The main obstacles lie in the complexity of administrative procedures, limited access to tax facilities, and the lack of specific outreach regarding the tax treatment of Islamic financial instruments. These conditions have resulted in the benefits of tax incentives not being felt evenly by market participants. Therefore, efforts are needed to simplify regulations and increase legal certainty so that the tax burden on Sukuk Ijarah can be equivalent to conventional bonds, so that the principles of fairness and tax neutrality in the national taxation system can be realized.